1999
DOI: 10.1590/s0037-86821999000100013
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax resistance to chloroquine (R2) and mefloquine (R3) in Brazilian Amazon region

Abstract: Maria das Graças C. Alecrim, Wilson Alecrim and Vanize MacêdoResistência do Plasmodium vivax pela cloroquina (R2) e mefloquina (R3) na amazônia BrasileiraWe report for the first time R2 resistance to chloroquine and R3 resistance to mefloquine by P. vivax in the Brazilian Amazon region.FSS, a 12 year-old female patient from Autazes Municipality in the State of Amazonas, Brazil, was diagnosed as having P. vivax malaria on July 14 th 1997 (day 0) at the Instituto de Medicina Tropical do Amazonas, Manaus, Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 7 publications
0
62
0
6
Order By: Relevance
“…In Brazil, the first clinical evidence was reported in 2000 in Manaus (13). In Colombia, P. vivax CR was described in three cases among 27 subjects (14), and in Peru four cases were confirmed among 177 subjects (15).…”
mentioning
confidence: 98%
“…In Brazil, the first clinical evidence was reported in 2000 in Manaus (13). In Colombia, P. vivax CR was described in three cases among 27 subjects (14), and in Peru four cases were confirmed among 177 subjects (15).…”
mentioning
confidence: 98%
“…Los hallazgos enfatizan la importancia de diseñar estrategias para asegurar y vigilar el cumplimiento terapéutico, con el fin de garantizar la eficacia del tratamiento antipalúdico, cuando el medicamento se entrega a los pacientes con paludismo en los puestos de diagnóstico y tratamiento que son atendidos en su mayoría por microscopistas. A pesar de algunos informes de fallas terapéuticas en Guyana y Brasil (19,20), los resultados de los estudios de eficacia in vivo realizados hasta la fecha en Perú y Colombia (11,21,22,24,25) demuestran, en general, la eficacia de la cloroquina para el tratamiento del paludismo por P. vivax, a diferencia de lo informado en Papua, Nueva Guinea (17), y en Indonesia (18). De acuerdo con estos hallazgos, la resistencia de P. vivax a la cloroquina no constituye aún un serio problema en las Américas, aunque sí parece ser un problema emergente en la cuenca amazónica (15,19,20), mas no en las demás áreas endémicas de transmisión de paludismo en Colombia.…”
Section: Discussionunclassified
“…En las Américas, se han informado casos de fallas terapéuticas en Guyana (19) y Brasil (20). En un estudio realizado en Perú entre 1998 y 2001, con seguimiento de 28 días, se reportaron fallas en 4 de 177 pacientes (2,26%) con paludismo por P. vivax tratados con cloroquina en la región amazónica y ninguna falla en 59 pacientes evaluados al norte de la costa del Pacífico peruano (21).…”
unclassified
“…Some national studies have indicated the need for novel therapeutic strategies to circumvent the problem of chloroquine resistance for the treatment of P. vivax malaria, which is estimated at 5-10% in Manaus (34) (35) . It is possible that, in the short term, we may have to make use of artemisinin-based combination therapies (ACTs) as the fi rst choice in the State of Amazonas, although other states have not reported cases of chloroquine resistance, which is expected in large areas such as the Brazilian Amazon.…”
Section: Treatmentmentioning
confidence: 99%